Tight-binding Calculations of Band Structure and Conductance in Graphene Nano-ribbons - Tien, Hoang Manh; Chau, Nguyen Hai; Loan, Phan Thi Kim (Communications in Physics, 2009)
We suggest a general approach based on the nearest-neighbor tight-binding approximation (TB) to investigate the band structure and conductance of a quasi-one dimensional system. Numerical calculations carried out for Graphene nanoribbons (GNRs) with different widths and edge conditions (zigzag and armchair) reveal the well-known results that the electronic properties of GNRs depend strongly on the size and geometry of the sample.